A glass fiber reinforced PP / PA alloy material and its preparation method and application
By controlling the viscosity and relative ratio of PP resin and PA resin and combining with an appropriate amount of glass fiber, a glass fiber-reinforced PP/PA alloy material with high strength, good toughness and good screw-making performance was prepared, which solved the existing materials in electric power The problem of insufficient strength and toughness in tool application has achieved a comprehensive improvement in material performance.
Patent Information
- Application Number
- CN202311271823.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The existing glass fiber reinforced polypropylene/nylon alloy materials are insufficient in power tool applications, and poor compatibility lead to poor dispersion effect, which is unable to effectively exert the enhancement effect.
By controlling the viscosity range and viscosity ratio of PP resin and PA resin, combined with the usage and distribution of glass fibers, a glass fiber-reinforced PP/PA alloy material with high strength, good toughness and good screw-making performance was prepared.
The comprehensive performance improvement of glass fiber reinforced PP/PA alloy materials in power tool applications has been achieved, including the improvement of tensile strength, impact resistance and drop performance.
Smart Images

Figure BDA0004475771130000021 
Figure BDA0004475771130000051 
Figure BDA0004475771130000061
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of modified plastics, and relates to a glass fiber reinforced PP / PA alloy material and a preparation method and application thereof, and specifically relates to a glass fiber reinforced PP / PA alloy material for electric tools and a preparation method thereof. Background Art
[0002] Polypropylene (PP) resin, as a type of general-purpose plastic, has the advantages of low density, fatigue resistance, excellent chemical stability, and easy processing and molding. As the application fields of polypropylene materials gradually expand, the engineering of polypropylene has become a research hotspot.
[0003] The structural parts in power tool products have high requirements for material strength and toughness in order to cope with more complex operating conditions. Typical test items include ultimate strength, drop, screw driving, etc. The usual material is glass fiber reinforced nylon (PA). The use of polypropylene is greatly restricted due to insufficient strength and temperature resistance, or insufficient toughness.
[0004] Alloying is an important way to improve the performance of polypropylene materials and has become an important means of engineering modification of general plastics, which can achieve the effect of "taking advantage of others' strengths and overcoming their weaknesses".
[0005] The key to preparing alloy materials is to achieve good compatibility between different resins. At present, the main technical solution for polypropylene alloy materials is to add a compatibilizer to the system to improve the compatibility of the two phases. However, since polypropylene is a non-polar resin, it has poor compatibility with other polar resins such as nylon, PC, PBT, etc. Even by adding various compatibilizers, it is difficult to fundamentally improve the compatibility of the alloy. Microscopically, it is still in a phase-separated state, and the dispersed phase cannot achieve a good dispersion effect. The macroscopic mechanical properties (strength, toughness) of the prepared alloy material are poor, especially in the glass fiber reinforced system, and the reinforcement and toughening effects of nylon and glass fiber cannot be effectively exerted.
[0006] Therefore, it is desirable in the art to develop a glass fiber reinforced PP / PA alloy material with good dispersibility and balanced rigidity and toughness. Summary of the invention
[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a glass fiber reinforced PP / PA alloy material and a preparation method and application thereof, and specifically to provide a glass fiber reinforced PP / PA alloy material for electric tools and a preparation method thereof.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a glass fiber reinforced PP / PA alloy material, wherein the glass fiber reinforced PP / PA alloy material comprises the following components in parts by weight:
[0010]
[0011] The PP resin was heated at 230°C and a shear rate of 10 2 s -1 The apparent viscosity is 3500-9500 Pa·s;
[0012] The relative viscosity of the PA resin is 2.0-2.8;
[0013] Furthermore, the PP resin is heated to 230°C and a shear rate of 10 2 s -1 The ratio of the apparent viscosity to the relative viscosity of the PA resin is 2000-4500.
[0014] In the glass fiber reinforced PP / PA alloy material, the content of PP resin is not less than 29wt%.
[0015] In the present invention, PP resin is heated at 230°C and a shear rate of 10 2 s -1 The apparent viscosity was obtained by using a rotational rheometer at a test temperature of 230°C and a shear rate of 10 2 s -1 .
[0016] In the present invention, the relative viscosity test method of PA resin is as follows: weigh 0.5g PA resin, transfer it to a 50mL volumetric flask, add about 40mL of 96% mass fraction concentrated sulfuric acid, and ultrasonically oscillate until the PA resin is completely dissolved, cool the solution to 25°C, dilute it to the scale with concentrated sulfuric acid, and mix it evenly, test the flow time of 0.01g / mL PA resin solution through the Ubbelohde viscometer at 25°C, record it as t1, test the flow time of the solvent concentrated sulfuric acid with the same viscometer, record it as t2, and t1 / t2 is the relative viscosity.
[0017] In the present invention, by limiting the apparent viscosity of the PP resin and the relative viscosity of the PA resin within a certain range, and controlling the viscosity ratio of the two within a certain range, the dispersed phase has a good dispersion effect, and the prepared glass fiber reinforced PP / PA alloy material has high strength, good toughness and good screw driving performance.
[0018] In the present invention, the glass fiber reinforced PP / PA alloy material is measured in parts by weight, and the amount of PP resin used can be 33 parts, 34 parts, 35 parts, 38 parts, 40 parts, 43 parts, 45 parts, 48 parts, 50 parts, 53 parts, 55 parts, 58 parts, 60 parts, 63 parts, 65 parts or 68 parts, etc.
[0019] In the present invention, the glass fiber reinforced PP / PA alloy material is measured in parts by weight, and the amount of PA resin used can be 13 parts, 15 parts, 18 parts, 20 parts, 23 parts, 25 parts, 28 parts, 30 parts, 33 parts, 34 parts, 35 parts or 38 parts, etc.
[0020] In the present invention, the glass fiber reinforced PP / PA alloy material can be used in an amount of 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts or 11 parts by weight.
[0021] In the present invention, the glass fiber reinforced PP / PA alloy material can be used in an amount of 13 parts, 15 parts, 18 parts, 20 parts, 23 parts, 25 parts, 28 parts, 30 parts or 31 parts by weight.
[0022] The PP resin was heated at 230°C and a shear rate of 10 2 s -1 The apparent viscosity at the above-mentioned value can be, for example, 3500Pa·s, 4000Pa·s, 4500Pa·s, 5000Pa·s, 5500Pa·s, 6000Pa·s, 6500Pa·s, 7000Pa·s, 7500Pa·s, 8000Pa·s, 8500Pa·s, 9000Pa·s or 9500Pa·s.
[0023] The relative viscosity of the PA resin may be, for example, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7 or 2.8.
[0024] The PP resin was heated at 230°C and a shear rate of 10 2 s -1 4000, 4100, 4200, 4300, 4400 or 4500, etc.
[0025] Preferably, the PP resin is heated at 230°C and a shear rate of 10 2 s-1 The apparent viscosity of the PA resin is 4000-8600 Pa·s at 230°C and a shear rate of 10 2 s -1 The ratio of the apparent viscosity to the relative viscosity of the PA resin is 2500-4300.
[0026] Preferably, the PP resin includes any one of homopolymer polypropylene, block copolymer polypropylene or random copolymer polypropylene, or a combination of at least two of them.
[0027] Preferably, the PA resin includes any one of PA6 resin, PA66 resin, PA11 resin, PA12 resin, PA46 resin, PA610 resin, PA612 resin or PA1010 resin, or a combination of at least two thereof, preferably PA6 resin and / or PA66 resin.
[0028] Preferably, the compatibilizer comprises maleic anhydride grafted polypropylene, wherein the grafting rate of maleic anhydride is 0.8%-1.6%, for example, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5% or 1.6%, etc.
[0029] Preferably, the glass fibers include chopped alkali-free glass fibers.
[0030] Preferably, the original average length of the glass fiber is 3-6 mm, for example, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, 5.5 mm or 6 mm, and the average diameter of the glass fiber is 10-15 μm, for example, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm or 15 μm, etc.
[0031] Preferably, the glass fiber reinforced PP / PA alloy material also includes an antioxidant.
[0032] Preferably, the weight portion of the antioxidant is 0.1-0.6 parts, such as 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts or 0.6 parts.
[0033] Preferably, the antioxidant comprises tris(2,4-di-tert-butylphenol) phosphite (Antioxidant 168) and / or pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (Antioxidant 1010).
[0034] Preferably, in the glass fiber reinforced PP / PA alloy material, the average retained length of the glass fiber is 0.23-0.48 mm, for example, 0.23 mm, 0.24 mm, 0.25 mm, 0.26 mm, 0.27 mm, 0.28 mm, 0.29 mm, 0.30 mm, 0.31 mm, 0.32 mm, 0.33 mm, 0.34 mm, 0.35 mm, 0.36 mm, 0.37 mm, 0.38 mm, 0.39 mm, 0.40 mm, 0.41 mm, 0.42 mm, 0.43 mm, 0.44 mm, 0.45 mm, 0.46 mm, 0.47 mm, 0.48 mm, etc., preferably 0.30-0.40 mm.
[0035] As a preferred technical solution of the present invention, the average retention length of the glass fiber is controlled within the range of 0.23-0.48 mm, which can improve the comprehensive performance of the glass fiber reinforced PP / PA alloy material, so that the tensile properties, impact resistance and drop performance of the alloy material are all improved. Because the glass fiber will react with other materials and break during the melt extrusion process after being put into the screw extruder, the average retention length of the glass fiber can be controlled within the range of 0.23-0.48 mm by controlling the screw speed, screw combination, feed port position, feeding method (double-side feeding method, PA resin main feeding, PP resin first side feeding, glass fiber second side feeding) and other factors. The average retention length of the glass fiber can also be controlled within the range of 0.23-0.48 mm by controlling other factors such as the original length of the glass fiber, the ratio of the apparent viscosity of the PP resin to the relative viscosity of the PA resin.
[0036] In the present invention, the test method for the average retention length of glass fibers is as follows: a glass fiber reinforced PP / PA alloy material is calcined in a muffle furnace at 850° C. for 30 minutes, and then the glass fiber ash is placed under a microscope to count the average retention length of the glass fibers, and the number of counts is 600.
[0037] As a preferred technical solution of the present invention, the glass fiber reinforced PP / PA alloy material comprises the following components in parts by weight:
[0038]
[0039]
[0040] In a second aspect, the present invention provides a method for preparing the glass fiber reinforced PP / PA alloy material as described in the first aspect, the preparation method comprising the following steps:
[0041] (1) mixing a formulated amount of PA resin, a compatibilizer, and an optional antioxidant to obtain a premix;
[0042] (2) placing the premix obtained in step (1) at the main feed port of a twin-screw extruder, placing the PP resin at the first side feed port of the twin-screw extruder, placing the glass fiber at the second side feed port of the twin-screw extruder, and performing melt blending and extrusion granulation to obtain the glass fiber reinforced PP / PA alloy material.
[0043] Alternatively, the preparation method comprises the following steps:
[0044] (a) mixing formulated amounts of PA resin, PP resin, compatibilizer, and optional antioxidant to obtain a premix;
[0045] (b) placing the premix obtained in step (a) at the main feed port of a twin-screw extruder, placing the glass fiber at the side feed port of the twin-screw extruder, and performing melt blending and extrusion granulation to obtain the glass fiber reinforced PP / PA alloy material.
[0046] Preferably, the PA resin, compatibilizer, and optional antioxidant are dried before mixing. That is, whether the first preparation method or the second preparation method is adopted, the PA resin, compatibilizer, and optional antioxidant can be dried before mixing.
[0047] Preferably, the mixing in step (1) and step (a) is carried out in a high-speed mixer.
[0048] Preferably, the rotation speed of the high-speed mixer is 400-800 rpm, such as 400 rpm, 500 rpm, 600 rpm, 700 rpm or 800 rpm, and the mixing time is 15-30 min, such as 15 min, 18 min, 20 min, 23 min, 25 min, 28 min or 30 min, etc.
[0049] Preferably, the screw speed of the twin-screw extruder is 300-450 rpm, for example, 300 rpm, 330 rpm, 350 rpm, 380 rpm, 400 rpm, 430 rpm or 450 rpm.
[0050] Preferably, the melting temperature is 220-280°C, for example, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C or 280°C.
[0051] In a third aspect, the present invention provides a use of the glass fiber reinforced PP / PA alloy material as described in the first aspect in a power tool handle, a power tool housing or office supplies.
[0052] Preferably, the electric tool comprises a grinding electric tool and / or an assembly electric tool.
[0053] Preferably, the office supplies include office chairs.
[0054] Compared with the prior art, the present invention has at least the following beneficial effects:
[0055] In the present invention, by limiting the apparent viscosity of the PP resin and the relative viscosity of the PA resin within a certain range, and controlling the viscosity ratio of the two within a certain range, the dispersed phase has a good dispersion effect, and the prepared glass fiber reinforced PP / PA alloy material has high strength, good toughness and good screw driving performance. DETAILED DESCRIPTION
[0056] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0057] The specific raw materials used in the examples and comparative examples of the present invention, their brands and manufacturers are shown in Table 1.
[0058] Table 1
[0059]
[0060]
[0061] In Table 1, PP resin 1, PP resin 2, PP resin 3, and PP resin 5 are all block copolymer PP resins, and PP resin 4 is a homopolymer PP resin.
[0062] Embodiments 1-5 and Embodiment 8
[0063] In Examples 1-5 and Example 8, a glass fiber reinforced PP / PA alloy material is provided respectively. The specific components and amounts (in parts by weight) of the glass fiber reinforced PP / PA alloy material are shown in Table 2.
[0064] The preparation method comprises the following steps:
[0065] (1) Weigh each component according to the formula;
[0066] (2) mixing the dried PA6 resin, compatibilizer, and antioxidant in a high-speed mixer to obtain a premix; wherein the speed of the high-speed mixer is 500 rpm and the mixing time is 20 min;
[0067] (3) placing the premix obtained in step (2) at the main feed port of a twin-screw extruder, placing the PP resin at the first side feed port of the twin-screw extruder, and placing the glass fiber at the second side feed port of the twin-screw extruder, and performing melt blending and extrusion granulation to obtain the glass fiber reinforced PP / PA alloy material; wherein the screw speed of the twin-screw extruder is 400 rpm, and the melt temperature of the extruder is set to 240°C.
[0068] Example 6
[0069] In this embodiment, a glass fiber reinforced PP / PA alloy material is provided. The specific components and usage (parts by weight) of the glass fiber reinforced PP / PA alloy material are shown in Table 2.
[0070] The preparation method comprises the following steps:
[0071] (1) Weigh each component according to the formula;
[0072] (2) mixing the dried PA66 resin, compatibilizer, and antioxidant in a high-speed mixer to obtain a premix; wherein the speed of the high-speed mixer is 500 rpm and the mixing time is 20 min;
[0073] (3) placing the premix obtained in step (2) at the main feed port of a twin-screw extruder, placing the PP resin at the first side feed port of the twin-screw extruder, and placing the glass fiber at the second side feed port of the twin-screw extruder, and performing melt blending and extrusion granulation to obtain the glass fiber reinforced PP / PA alloy material; wherein the screw speed of the twin-screw extruder is 450 rpm, and the melt temperature of the extruder is set to 280°C.
[0074] Example 7
[0075] The difference between this embodiment and embodiment 2 is that the preparation method is different, and the preparation method is as follows:
[0076] (1) Weigh each component according to the formula;
[0077] (2) mixing the dried PA6 resin, PP resin, compatibilizer, and antioxidant in a high-speed mixer to obtain a premix; wherein the speed of the high-speed mixer is 500 rpm and the mixing time is 20 min;
[0078] (3) placing the premix obtained in step (2) at the main feed port of a twin-screw extruder, placing the glass fiber at the side feed port of the twin-screw extruder, and performing melt blending and extrusion granulation to obtain the glass fiber reinforced PP / PA alloy material; wherein the screw speed of the twin-screw extruder is 400 rpm, and the melt temperature of the extruder is set to 240°C.
[0079] Comparative Examples 1-4
[0080] In Comparative Examples 1-4, a glass fiber reinforced PP / PA alloy material is provided respectively. The specific components and amounts (parts by weight) of the glass fiber reinforced PP / PA alloy materials are shown in Table 2.
[0081] The preparation method is the same as that of Example 1-5.
[0082] The glass fiber reinforced PP / PA alloy materials prepared in the examples of the present invention and the comparative examples were subjected to performance tests, and the test methods were as follows:
[0083] (1) Tensile strength: The tensile strength of the material was tested according to ISO 527-2012 standard at a tensile speed of 10 mm / min;
[0084] (2) Screw torque test: The torque test uses M5 self-tapping screws with an outer diameter of 5 mm, an inner diameter of 4.12 mm, an outer diameter of 9.8 mm, and a wall thickness of 5.68 mm. The ultimate torque of the alloy material is tested until the screw column is stripped or cracked. The maximum torque value is recorded. The larger the torque value, the better the screw performance.
[0085] (3) Drop performance evaluation adopts the drop ball impact method. The material is injection molded into a 100*100*2mm square plate. A steel ball weighing 1000g is used to perform drop ball impact tests at different heights. The lowest height at which the square plate cracks is recorded. The higher the height, the better the drop performance of the material.
[0086] The performance test results are shown in Table 2.
[0087] Table 2
[0088]
[0089]
[0090] It can be seen from Table 2 that the glass fiber reinforced PP / PA alloy material provided in the embodiment of the present invention not only has excellent strength (tensile strength ≥ 95MPa), but also has good toughness (notch impact strength ≥ 15KJ / m 2 ), the screw torque test performance is good (limit torque ≥3.62N·m), and the falling ball impact performance is good (falling ball impact height is ≥125mm), which shows that nylon has a good dispersion effect in the alloy system.
[0091] Compared with Example 4, the tensile strength, notched impact strength and falling ball impact height of the glass fiber reinforced PP / PA alloy materials provided in Comparative Examples 1, 3 and 4 are all decreased. Compared with Example 3, the tensile strength, notched impact strength and falling ball impact height of the glass fiber reinforced PP / PA alloy materials provided in Comparative Example 2 are all decreased, which indicates that the PP resin has a good thermal conductivity at 230°C and a shear rate of 10 2 s -1 The ratio of the apparent viscosity under the conditions of 100 μm to the relative viscosity of the PA resin is within a specific range, and the prepared glass fiber reinforced PP / PA alloy material has good comprehensive performance. In addition, it can be seen from the average retention length data of the glass fibers in the embodiments and comparative examples that, unlike the ordinary glass fiber reinforced single resin system in which the longer the average retention length of the glass fiber, the better the performance, in the alloy system provided by the present invention, the viscosity ratio of the system is combined, and the average retention length of the glass fiber is achieved within a certain range at the same time, and the performance is greatly improved.
[0092] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the glass fiber reinforced PP / PA alloy material and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A glass fiber reinforced PP / PA alloy material, characterized in that: The glass fiber reinforced PP / PA alloy material comprises the following components in parts by weight: PP resin 33-68 parts; 13-38 parts of PA resin; 4-11 parts of compatibilizer; Glass fiber 13-31 parts; The PP resin was heated at 230°C and a shear rate of 10 2 s -1 The apparent viscosity under 3500-9500 Pa·s; The relative viscosity of the PA resin is 2.0-2.8; Furthermore, the PP resin is heated to 230°C and a shear rate of 10 2 s -1 The ratio of the apparent viscosity to the relative viscosity of the PA resin is 2000-4500; The relative viscosity test method of the PA resin is as follows: weigh 0.5g of PA resin, transfer it to a 50mL volumetric flask, add 40mL of 96% by mass concentrated sulfuric acid, and perform ultrasonic oscillation until the PA resin is completely dissolved. The solution is cooled to 25°C, diluted to the scale with concentrated sulfuric acid, and mixed evenly. The flow time of 0.01g / mL PA resin solution passing through the Ubbelohde viscometer at 25°C is measured, which is recorded as t1. The flow time of the solvent concentrated sulfuric acid is measured using the same viscometer, which is recorded as t2. t1 / t2 is the relative viscosity. The average retention length of the glass fiber is 0.30-0.40 mm; The test method for the average retention length of the glass fiber is as follows: the glass fiber reinforced PP / PA alloy material is placed in a muffle furnace at 850° C. and calcined for 30 minutes, and then the glass fiber ash is placed under a microscope to count the average retention length of the glass fiber, and the number of counts is 600.
2. The glass fiber reinforced PP / PA alloy material according to claim 1, characterized in that: The PP resin was heated at 230°C and a shear rate of 10 2 s -1 The apparent viscosity of the PA resin is 4000-8600 Pa·s at 230°C and a shear rate of 10 2 s -1 The ratio of the apparent viscosity to the relative viscosity of the PA resin is 2500-4300.
3. The glass fiber reinforced PP / PA alloy material according to claim 1, wherein the PP resin comprises any one of homopolymer polypropylene, block copolymer polypropylene or random copolymer polypropylene, or a combination of at least two of them.
4. The glass fiber reinforced PP / PA alloy material according to claim 1, characterized in that: The PA resin includes any one of PA6 resin, PA66 resin, PA11 resin, PA12 resin, PA46 resin, PA610 resin, PA612 resin or PA1010 resin, or a combination of at least two of them.
5. The glass fiber reinforced PP / PA alloy material according to claim 1, characterized in that: The PA resin is PA6 resin and / or PA66 resin.
6. The glass fiber reinforced PP / PA alloy material according to claim 1, characterized in that: The compatibilizer includes maleic anhydride grafted polypropylene, wherein the grafting rate of maleic anhydride is 0.8%-1.6%.
7. The glass fiber reinforced PP / PA alloy material according to claim 1, characterized in that: The glass fibers include chopped alkali-free glass fibers.
8. The glass fiber reinforced PP / PA alloy material according to claim 1, characterized in that: The original average length of the glass fibers is 3-6 mm, and the average diameter of the glass fibers is 10-15 μm.
9. The glass fiber reinforced PP / PA alloy material according to claim 1, characterized in that: The glass fiber reinforced PP / PA alloy material also includes an antioxidant.
10. The glass fiber reinforced PP / PA alloy material according to claim 9, characterized in that: The weight portion of the antioxidant is 0.1-0.6 parts.
11. The glass fiber reinforced PP / PA alloy material according to claim 9, characterized in that: The antioxidant includes tris(2,4-di-tert-butylphenol) phosphite and / or pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate.
12. The glass fiber reinforced PP / PA alloy material according to claim 1, characterized in that: The glass fiber reinforced PP / PA alloy material comprises the following components in parts by weight: PP resin 34-60 parts; 18-35 parts of PA resin; Compatibilizer 5-10 parts; Glass fiber 18-30 parts; Antioxidant 0.2-0.4 parts.
13. A method for preparing a glass fiber reinforced PP / PA alloy material according to any one of claims 1 to 12, characterized in that: The preparation method comprises the following steps: (1) Mixing the formulated amount of PA resin, compatibilizer, and optional antioxidant to obtain a premix; (2) placing the premix obtained in step (1) at the main feed port of a twin-screw extruder, placing the PP resin at the first side feed port of the twin-screw extruder, placing the glass fiber at the second side feed port of the twin-screw extruder, and performing melt blending and extrusion granulation to obtain the glass fiber reinforced PP / PA alloy material; Alternatively, the preparation method comprises the following steps: (a) mixing the formulated amounts of PA resin, PP resin, compatibilizer, and optional antioxidant to obtain a premix; (b) placing the premix obtained in step (a) at the main feed port of a twin-screw extruder, placing the glass fiber at the side feed port of the twin-screw extruder, and performing melt blending and extrusion granulation to obtain the glass fiber reinforced PP / PA alloy material.
14. The preparation method according to claim 13, characterized in that: The PA resin, compatibilizer and optional antioxidant in step (1) and step (a) are dried before mixing.
15. The preparation method according to claim 13, characterized in that: The mixing in step (1) and step (a) is carried out in a high-speed mixer.
16. The preparation method according to claim 15, characterized in that: The rotation speed of the high-speed mixer is 400-800 rpm, and the mixing time is 15-30 min.
17. The preparation method according to claim 13, characterized in that: The screw speed of the twin-screw extruder in step (2) and step (b) is 300 to 450 rpm.
18. The preparation method according to claim 13, characterized in that: The melting temperature in step (2) and step (b) is 220-280°C.
19. Use of the glass fiber reinforced PP / PA alloy material according to any one of claims 1 to 12 in a power tool handle, a power tool housing or office supplies.
20. The use according to claim 19, characterized in that The electric tool comprises a grinding electric tool and / or an assembly electric tool.
21. The use according to claim 19, characterized in that The office supplies include office chairs.
Citation Information
Patent Citations
Alloy material with ceramized surface as well as preparation method and application of alloy material
CN112745573A
Fiber-reinforced resin composition and molded article
CN116406400A
fiber-reinforced thermoplastic semi-finished product
DE112007001779A5
Polypropylene composition
JP1994179784A
Matte film
JP1998158445A
Cited By
PP / PA composite material for automobile front-end module and preparation method of PP / PA composite material
CN121873475A
PP / PA composite material for automobile front end module and preparation method thereof
CN121873475B